Evidence for loss of a partial flagellar glycolytic pathway during trypanosomatid evolution. - Robert W B Brown; Peter W Collingridge; Keith Gull; Daniel J Rigden; Michael L Ginger (PLoS ONE)
Classically viewed as a cytosolic pathway, glycolysis is increasingly recognized as a metabolic pathway exhibiting surprisingly wide-ranging variations in compartmentalization within eukaryotic cells. Trypanosomatid parasites provide an extreme view of glycolytic enzyme compartmentalization as several glycolytic enzymes are found exclusively in peroxisomes. Here, we characterize Trypanosoma brucei flagellar proteins resembling glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and phosphoglycerate kinase (PGK): we show the latter associates with the axoneme and the former is a novel paraflagellar rod component. The paraflagellar rod is an essential extra-axonemal structure in trypanosomes and related protists, providing a platform into which metabolic activities can be built. Yet, bioinformatics interrogation and structural modelling indicate neither the trypanosome PGK-like nor the GAPDH-like protein is catalytically active. Orthologs are present in a free-living ancestor of the trypanosomatids, Bodo saltans: the PGK-like protein from B. saltans also lacks key catalytic residues, but its GAPDH-like protein is predicted to be catalytically competent. We discuss the likelihood that the trypanosome GAPDH-like and PGK-like proteins constitute molecular evidence for evolutionary loss of a flagellar glycolytic pathway, either as a consequence of niche adaptation or the re-localization of glycolytic enzymes to peroxisomes and the extensive changes to glycolytic flux regulation that accompanied this re-localization. Evidence indicating loss of localized ATP provision via glycolytic enzymes therefore provides a novel contribution to an emerging theme of hidden diversity with respect to compartmentalization of the ubiquitous glycolytic pathway in eukaryotes. A possibility that trypanosome GAPDH-like protein additionally represents a degenerate example of a moonlighting protein is also discussed.